Penerapan Konseling Individu Dengan Pendekatan Humanistik Dalam Mengatasi Insecure (Studi Kasus Korban Bullying Klien “G”) - Vira Pratiwi (Journal of Society Counseling, 2023)
This research entitled "Implementation of Individual Counseling With Approach Humanistic in Overcoming Insecure (Case Study of Client Bullying Victims “G”)”. Insecure is acondition where individuals feel Insecure, unsure, afraid, anxious and so on. This research aims to knowing the description of Insecure victims of bullying clients "G" and for know the application of individual counseling with a humanistic approach in dealing with Insecure victims of bullying client "G". This research using a qualitative approach with a case study research method. The subjects in this study were clients "G". Data collection techniques used consists of three techniques namely observation, interviews and documentation. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. As for the results This study shows that the image of Insecure clients "G" is the client "G" feels unhappy, feels Insecure, doubts about ability, feeling unable to do something, feeling guilty, easily anxious, experiencing body image disturbance, withdrawing from social environment, often alone because of embarrassment, and choose not to socialize. Application of individual counseling using the approach humanistic with client centered technique is done 6 times meetings with a time of 45x/meeting. Implementation of this individual counseling carried out in three stages, namely, the initial stage, the core/work stage, and the final stage end.